An Exploratory Study of Volunteer Stress Management: The organisational story - Holmes, Kirsten; Lockstone-Binney, L. (Australian and New Zealand Third Sector Research Inc., 2014)
Studies of volunteer stress, its causes and how it is dealt with, from the perspective of organisations that manage volunteers, are limited. This paper presents an exploratory study that complements the existing, more prevalent literature on volunteer stress and burnout from the volunteer perspective. A convenience sample of practitioners attending a national volunteering conference yielded 49 participants for the study. Findings indicate that role overload, competing work and family pressures and inter-volunteer conflicts are the most prominent sources of volunteer stress that volunteer-involving organisations are called on to manage. The associated implications for organisations and the broader sector are discussed.